A Study on the Criteria for Judging Acquired Distinctiveness as a Result of Using the Trademark - Taemin Eom (Journal of Intellectual Property)
This article contributes to the examination of recent developments, challenges, and controversies concerning the criteria for judging the distinctiveness of a mark acquired through use. The article explains that South Korea, the United States, the European Union and Japan introduced a provision in their Acts to allow registration if a mark acquired distinctiveness through use. Subsequently, it shows the standards required for acquisition of distinctiveness through use are the highest for the examinations and decrease in the order of the court cases and Intellectual Property Trial and Appeal Board’s decisions. This article concludes the following: First, even for marks known only in a certain region, recognition of the acquisition of distinctiveness through use should be established as court precedents. Second, in the appeal trial of mark registration, the claim of acquired distinctiveness through use should be incorporated into the Trial Handling Regulations as a subject of a five-judge agreement. Third, the Trademark Examination Handling Regulations must specify the legal basis for the Examination Committee for the Determination of Acquisition of Distinctiveness through Use and the participation of the examiners in charge. Fourth, the basis for recognizing facts in court precedents as valid evidence in examination procedures must be stated in the Examination Guidelines for Trademarks.